Meteorite‐Assisted Phosphorylation of Adenosine Under Proton Irradiation Conditions. Issue 3 (21st October 2019) - Bizzarri, Bruno M.; Šponer, Judit E.; Šponer, Jiri; Cassone, Giuseppe; Kapralov, Michail; Timoshenko, Gennady N.; Krasavin, Eugene; Fanelli, Giuseppina; Timperio, Anna Maria; Di Mauro, Ernesto; Saladino, Raffaele
Abstract: The abiotic phosphorylation of nucleosides is a major hurdle in origin‐of‐life studies. We suggest a plausible pathway for the synthesis of adenosine nucleotides from adenosine and NaH2 PO4 under radiative conditions mimicking the solar wind in the presence of a meteorite of the aubrite‐type. Hydroxyapatite also performed as a mineral heterogeneous phosphorus source. Adenosine polyphosphate derivatives and inorganic polyphosphates were detected in the reaction mixture, highlighting the high reactivity of the system. Both the total yield of adenosine nucleotides and the conversion of adenosine increased upon performing the irradiation in the presence of formamide (NH2 CHO) and aubrite. These experiments simulate conditions in space or on an early Earth fluxed by protons from the solar wind, potentially mimicking a plausible prebiotic phosphorylation scenario. Abstract : An old bond : A meteorite of the aubrite type catalyzed the phosphorylation of nucleosides to nucleotides in the presence of orthophosphate, formamide and proton beams, mimicking the effect of the solar wind on prebiotic phosphorylation processes. The reaction occurred also with hydroxyapatite as a well‐recognized phosphorus mineral source on the Primitive Earth. Polyphosphate condensation and radical pathways emerged from experimental data and theoretical calculations as effective reaction pathways.